The Perceptions of Entrepreneurs on the Strategic Role of Human Resource Management - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
In literature, many researches on human resource management and entrepreneurship have been developed. However, there are only few researches on the perception of entrepreneurs on the strategic role of human resource management. This study investigates the role of human resource management on developing sustainable entrepreneurship and describes how human resource management practices and procedures can be used to help entrepreneurs to navigate their companies. Furthermore this study was applied to 85 entrepreneurs who attended Entrepreneur Support Programme in the Aegean Region of Turkey, supported by the Republic of Turkey Small and Medium Enterprises Development Organization (KOSGEB) in 2011. The obtained data from the questionnaires are analyzed through SPSS for Windows 17.0. It is resulted from the study that entrepreneurs have positive approaches toward human resource management contrary to our biases during the pre survey period about entrepreneurs' perceptions. Before conducting the survey, it was expected from entrepreneurs that money is the first important motivator for their start-up firms. However, results of the survey indicate that human is more important rather than money for entrepreneurs. On the other hand, surprisingly, entrepreneurs have at least average level knowledge on human resource management and its functions.
Keywords: Human resource managemet; entrepreneurship; entrepreneur; small business and self employment; management; manager; business; human resource functions